Enhancement of the Texture & Morphology of Nano γ-Alumina as a Support for Naphtha Reforming Catalyst - Flayyih, Mustafa H.; Theib, Mohammed S. (Journal of Petroleum Research and Studies, 2023)
The morphology of nano gamma alumina affects the molecule adsorption-desorption phenomena. In this case, manipulating the surface area, pore volume, and pore size by the technique of preparation to control the morphology and textural properties of gamma alumina. Washing of the synthesized boehmite gel with methanol has a significant effect. The co-precipitation method was used to prepare nano gamma alumina, which is involved by adding drop-by-drop ammonium hydroxide and aluminum nitrate nonahydrate solutions to a cetyltrimethylammonium bromide (CTAB) cationic surfactant solution at 30 C and adjust PH to 8. Nitrogen adsorption-desorption analysis (ASAP 2020), Atomic Force Microscope (AFM), and X-Ray Diffraction (XRD) were used to examine the obtained material. Surface area (362 m2/g), pore volume (0.51 cm3/g), pore size (5.2 nm), and narrow pore size distribution were obtained.